2017
DOI: 10.1111/opo.12387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated refractive error on adult visual acuity for paediatric tests

Abstract: Although the Cardiff Acuity Test provides an easy method for VA measurement in infants and toddlers, there is a considerable overestimation of VA compared with recognition acuity tasks particularly in the presence of defocus. A simple correction factor (of for example three lines overestimate) cannot be applied to Cardiff acuity measures as there is increasing over-estimation of VA with increasing defocus. Infants with significant refractive error may fall within normal visual acuity ranges for the Cardiff Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…The Cardiff Acuity Test is useful for estimating acuity in very young children and those with cognitive difficulties (Adoh et al, 1992). However, results do not align well with recognition acuity tests using regular optotypes (Paudel et al, 2017), perhaps due to perception of vanishing compared to regular optotypes, or perhaps because of the testing protocol. It would therefore be useful to compare measures of acuity made with vanishing and regular versions of identical optotypes with the same test protocol, as has been done with Sloan letters (Shah et al, 2011;Shah et al, 2012;Shah, Anderson, Tufail, Egan, & Dakin, 2013;Shah et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…The Cardiff Acuity Test is useful for estimating acuity in very young children and those with cognitive difficulties (Adoh et al, 1992). However, results do not align well with recognition acuity tests using regular optotypes (Paudel et al, 2017), perhaps due to perception of vanishing compared to regular optotypes, or perhaps because of the testing protocol. It would therefore be useful to compare measures of acuity made with vanishing and regular versions of identical optotypes with the same test protocol, as has been done with Sloan letters (Shah et al, 2011;Shah et al, 2012;Shah, Anderson, Tufail, Egan, & Dakin, 2013;Shah et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…45 Previously research has shown nearly equal VA reductions with induced spherical and cylindrical defocus for both letter optotypes and Lea symbols. 46 Furthermore, the lower specificity of the Parr vision test compared with the Lea symbols indicates a larger number of false positive results, thereby suggesting a lower number of correct guesses at threshold. The results of the current study indicate the Parr vision test provides an acceptable paediatric vision screening tool, with a shorter testing time than Lea symbols.…”
Section: Discussionmentioning
confidence: 99%
“…The Cardiff Acuity Test is significantly less sensitive than recognition acuity tasks, such as the Lea Symbols, for detecting refractive errors. 18,19,30 Nevertheless, recognition acuity measures are difficult to achieve in children younger than 36 months 31 and cooperation for monocular visual acuity measures is particularly challenging. 32…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Nevertheless, vanishing optotypes may be more resistant to optical defocus than recognition acuity tasks and therefore may have reduced sensitivity for detecting refractive errors. 18,19 Consequently, automated preschool vision screening tests, such as autorefraction or the Pediatric Vision Screener 20 have been suggested as better screening methods for detecting amblyopia and/or amblyopia risk factors in 12-30 month old children. 21…”
Section: Introductionmentioning
confidence: 99%